Studi Analisis Pasca Pandemi: Pengaruh Pembelajaran PAI Secara Daring Terhadap Mental Spiritual Siswa SMP - Adila, Amma Chorida; Faiz, Muhammad; Mukhlis, Abdul M. (Edification Journal : Pendidikan Agama Islam, 2022)
Learning PAI online raises various problems that have an impact on students' mental and spiritual. The object of this research study is junior high school students because they have an unstable nature and patterns of thinking. The purpose of this study was to determine the problems of the impact of the weak mental and spiritual students. So that efforts can be made to develop students with the application of PAI subjects. This study uses descriptive qualitative methods in the analysis that has been carried out to solve post-pandemic problems. The results of this study indicate that the online learning provided by the teacher is expected to be effective and ideal. However, not all subjects can apply this because of the challenges and obstacles, especially in PAI lessons. Because there are 6 basic topics of discussion including Akidah-Akhlaq, Qur'an-Hadith, Fiqh, and History of Islamic Culture (SKI). Online learning on PAI subjects turned out to have an effect on students' mental and spiritual. Most students who are mentally and spiritually weak will have various disorders of morality. For this reason, there is a need for mental spiritual development from PAI learning such as advice from the al-Qur’an and Hadith.